PENGGUNAAN SIX SIGMA SEBAGAI EVALUASI KONTROL KUALITAS PADA ALAT HEMATOLOGY ANALYZER SYSMEX XN-550 - Nidianti, Della; Feisyal Rinaldi, Sonny; Rahmat, Mamat; Ridwanna, Surya (Politeknik Kesehatan Kemenkes Bandung, 2024)
Six Sigma uses defects per unit as the unit of measurement. Accordingly, the goal of this study is to ascertain the haematology parameters' sigma value, QC rule, and TEa value at the Pramita Lab Pajajaran Bandung Branch. This type of research is a descriptive analytic. The data used in tis study can be obtained from the results of Internal Quality Control in Pramita Lab, A total of 5 parameters were calculate bu Six Sigma using the Total Error Allowable (TEa) from Biological Variation and CLIA. TEA is mapped based on the area in the graph. Decision making for the selection of TEa is based on the TEa selection algorithm. Based on the results of the study, the precision on the parameters of hemoglobin, hematocrit, leukocytes, thrombocyte and erythrocytes was acceptable. The average of 6 months control value of Sigma the including the acquisition of world class ( > 6 sigma) consisting of parameters leukocytes so that QC rule is 1-3ss N=3, hemoglobin and erythrocytes obtain excellent ( 5 – 6 sigma ) so that QC rule is 2 of 3-2s and R4s N = 3. Hematocrit and thrombocyte obtain good ( 4 – 5 sigma) so that QC rule is 3-1s N = 3. The TEa from Desirable Biological Variation can be used for examination of thrombocyte. Minimal Biological Variation can be used for examination of erythrocytes. Optimal Biological variation can be used for examination of leukocytes. CLIA can be used for examination of Hemoglobin and hematocrit.